Evaluating the Effectiveness of Career Counselling: Recent Evidence and Recommended Strategies - Flynn, Robert J. (Canadian Journal of Counselling and Psychotherapy, 2007)
A recent national study of career and employment counselling in Canada (Conger, Hiebert & Hong-Farrell, 1994) showed that evaluation typically receives little attention. Encouragingly, meta-analyses conducted in the United States have indicated that career counselling produces positive effects and that these are, on the average, of the same magnitude as those brought about by well-developed psychological, educational, and behavioural interventions in general. Additional evaluative research is needed, however, to clarify the central questions of why career counselling is effective, with whom, underwhat conditions, and on which outcome dimensions. To encourage the investigation of these issues, selected process-oriented and outcome-oriented evaluation strategies described in the recent literature were presented. Illustrations of their application were drawn from the author's research and that of his students.